Association of Tobacco Use During Pregnancy, Perceived Stress, and Depression Among Alaska Native Women Participants in the Healthy Pregnancies Project. Issue 11 (30th September 2019) - Patten, Christi A; Lando, Harry A; Desnoyers, Chris A; Klejka, Joseph; Decker, Paul A; Bock, Martha J; Hughes, Christine A; Alexie, Lucinda; Boyer, Rahnia; Resnicow, Kenneth; Burhansstipanov, Linda
Abstract: Introduction: In general population samples, higher levels of stress and depression have been associated with increased prevalence of smoking in pregnancy. Little is known about the association of prenatal tobacco use, stress, and depression among American Indian or Alaska Native (AI/AN) women. Methods: The Healthy Pregnancies Project is a cluster-randomized controlled trial, evaluating a community-level intervention compared with usual care, for reducing tobacco use during pregnancy and postpartum among AN women in 16 villages in western Alaska. This cross-sectional study analyzed baseline data from enrolled pregnant women. Baseline measures included the self-reported, 7-day, point-prevalence current use of any tobacco, Perceived Stress Scale (PSS), and the Center for Epidemiological Studies-Depression (CES-D). Generalized estimating equations (GEE) analyses adjusted for village, participant age, and gestational age. Results: Participants ( N = 352) were on average (SD) 25.8 (5.0) years of age and at 26.8 (9.8) weeks gestation. 66.5% were current tobacco users, of which 77% used Iqmik, a homemade form of smokeless tobacco. Compared with nonusers, tobacco users reported lower PSS score ( p = .020) and less clinical levels of depression (CES-D ≥ 16) (18.1% vs. 9.3%, p = .21). Findings were not accounted for by nicotine dependence severity or self-reported tobacco use before pregnancy. Conclusions: In this sample of pregnant AN women, tobacco users report less stress and clinical levels of depression than nonusers. A potential challenge with tobacco treatment for pregnant AN women is to provide alternative ways of deescalating stress and affect management instead of using tobacco. Implications: This study contributes novel information on the association of tobacco use, perceived stress, and depression among Alaska Native women enrolled in a clinical trial to promote healthy pregnancies. Most prior studies addressing this topic were conducted among general population samples of pregnant women who smoked cigarettes. Little is known about these associations with prenatal smokeless tobacco, or among American Indian or Alaska Native women. The results are contrary to findings reported previously, because current tobacco use was associated with less stress and depression than nonuse. The study findings have implications for cessation treatment for this tobacco-use disparity group.